Cross-Circulation for Extracorporeal Liver Support in a Swine Model. Issue 4 (3rd August 2021) - Wu, Wei Kelly; Tumen, Andrew; Stokes, John W.; Ukita, Rei; Hozain, Ahmed; Pinezich, Meghan; O'Neill, John D.; Lee, Michael J.; Reimer, Jonathan A.; Flynn, Charles R.; Talackine, Jennifer R.; Cardwell, Nancy L.; et al.
Abstract : Although machine perfusion has gained momentum as an organ preservation technique in liver transplantation, persistent organ shortages and high waitlist mortality highlight unmet needs for improved organ salvage strategies. Beyond preservation, extracorporeal organ support platforms can also aid the development and evaluation of novel therapeutics. Here, we report the use of veno-arterial-venous (V-AV) cross-circulation (XC) with a swine host to provide normothermic support to extracorporeal livers. Functional, biochemical, and morphological analyses of the extracorporeal livers and swine hosts were performed over 12 hours of support. Extracorporeal livers maintained synthetic function through alkaline bile production and metabolic activity through lactate clearance and oxygen consumption. Beyond initial reperfusion, no biochemical evidence of hepatocellular injury was observed. Histopathologic injury scoring showed improvements in sinusoidal dilatation and composite acute injury scores after 12 hours. Swine hosts remained hemodynamically stable throughout XC support. Altogether, these outcomes demonstrate the feasibility of using a novel V-AV XC technique to provide support for extracorporeal livers in a swine model. V-AV XC has potential applications as a translational research platform and clinical biotechnology for donor organ salvage.